Capitalism and the History of Rural Java: The Dynamics of Economic and Political Oligarchy in Villages during the New Order - Pasang Budy All Shodiq Budy; Fernanda Prasky Hartono; Anis Syatul Hilmiah; Fachri Zulfikar; Nurul Umamah (Yupa: Historical Studies Journal, 2026)
This article examines the historical formation and strengthening of economic and political oligarchy in rural Java during the New Order within the framework of state capitalism. Using a critical historical approach, it analyzes historical literature, scholarly articles, and contemporary news through heuristic, verification, interpretation, and historiography. The study shows that New Order development policies, especially the Green Revolution and village standardization under Law No. 5 of 1979, turned villages into political and economic instruments of the state. Village elites acted as intermediaries between state interests and capital, producing oligarchic structures at the local level. This article argues that oligarchy in rural Java was historically shaped through development policy, capital penetration, and village power restructuring, thereby contributing to the historiography of rural political history in Indonesia.